2011
DOI: 10.1111/j.1471-0528.2011.03173.x
|View full text |Cite
|
Sign up to set email alerts
|

Medical simulation for professional development—science and practice

Abstract: From the earliest days of medical practice, when surgeons used cadavers to explore the possibilities of surgical intervention, simulation has been employed to advance the practice of health care. In the last 10 years, technological advances have allowed for a wider availability and greater realism of simulation, and this has encouraged a great expansion in its use. Simulation aims to create a virtuous cycle of professional development to improve patient outcomes. Although it seems eminently logical to believe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Role-play is used mainly for training in interviewing techniques [27] and other nontechnical skills such as communication [28,29]. An instructor and other students can be online too, so that discussions and team activities are feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Role-play is used mainly for training in interviewing techniques [27] and other nontechnical skills such as communication [28,29]. An instructor and other students can be online too, so that discussions and team activities are feasible.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that feedback and debriefing are the principle sources of learning in simulation training and that skilled feedback slows the rate of decay of clinical skills acquired via simulation‐based learning . It has been pointed out that embarrassment or fear of ridicule is major barrier to learning in simulation environments and that course participants have concerns in these areas prior to training . Small units can have practical difficulties in releasing staff from clinical duties to allow participation in training activities.…”
Section: Discussionmentioning
confidence: 99%
“…Nas últimas três a quatro décadas, o treinamento na área da saúde com o uso das estratégias de simulação tem crescido de forma exponencial em todo o mundo, levando a inovações tecnológicas e também a demandas orçamentárias crescentes [1][2][3][4][5]. Apesar de impulsionado pelo argumento legítimo de que o uso da simulação proporciona uma maior segurança aos pacientes, as evidências quanto a sua efetividade ainda não estão bem estabelecidas [6][7][8][9][10][11][12][13][14].…”
Section: Introductionunclassified